Characteristics of multicellular tumor spheroids formed by pancreatic cells expressing different adhesion molecules - Svirshchevskaya, Elena; Felix, Klaus M. (Life sciences, 2019)
Aims - Multicellular tumor spheroids (MCTS) produced by different methods vary in forms, sizes, and properties. The aim of this work was to characterize MCTS formed by six pancreatic cell lines on a non-adherent surface. - Materials and methods - Human pancreatic cells were grown in 2D and 3D conditions and compared for the expression of E- and desmosomal cadherins (PCR, confocal microscopy), growth, cell cycling, apoptosis (flow cytometry), and a response to antitumor drugs doxorubicin and gemcitabine (MTT-assay). - Key findings - Three types of MCTS were identified: BxPC-3, T3M4 formed small number of large and dense spheroids representing type I MCTS; COLO-357 and AsPC-1 generated type II multiple and loose MCTS of different sizes while MiaPaCa-2 and PANC-1 represented type III cultures which grew almost as floating monolayer films. Formation of type I MCTS depended on the simultaneous expression of DSG3 and several DSC proteins; II MCTS expressed solely DSG2-DSC2 but not DSG3, while type III cells either did not express E-cadherin or a pair of DSG and DSC proteins. Cells in type I MCTS but not in types II and III ones quickly became quiescent which correlated with a decrease in the proliferation, increased apoptosis, and a higher resistance to antitumor drugs doxorubicin and gemcitabine. - Significance - Taken collectively, pancreatic cells significantly vary in the expression of desmosomal cadherins, resulting in the formation of MCTS with different characteristics. The sensitivity of MCTS to various drugs depends on the type of cells and the method of spheroid preparation used.
Gesehen am 26.07.2019